Studi Komparatif Potensi Financial Distress pada Industri Rokok di BEI (Model Zscore Gover dan X Score Zmijewski) - Lizabeth Sari Dewi; Aulia Yunica Harly; Hasan Basri (Universitas Batanghari Jambi, 2022)
One of the state's opinions comes from excise payments made by cigarette companies in Indonesia, at the end of 2021 the issue of cigarette prices which will be increased in 2022 becomes an interesting phenomenon to study the potential for bankruptcy of cigarette companies listed on the Indonesia Stock Exchange. The purpose of this study is to analyze the potential for financial distress in cigarette companies and compare the results of the calculation of the springate and zmijewski models in cigarette companies on the Indonesia Stock Exchange. The research method used is quantitative descriptive analysis, with the data source coming from the company's annual report. The results showed that there was a potential for bankruptcy at PT. Bentoel Internasional Investama Tbk and PT. Wismilak Inti Makmur Tbk while for PT. Hm Sampoerna Tbk and PT. Gudang Garam Tbk has no potential for bankruptcy in 2017 to 2019, it's just that in 2020 the company PT. Bentoel Internasional Investama Tbk is experiencing financial difficulties. Based on the calculation results of the Springate and Zmisjewski models, there is also no difference from the results of the calculation of financial distress in cigarette companies on the Indonesia Stock Exchange.